The study local level supply in Malaysia construction industry : strategies in improvement - Md Khusairi, Baharun (2012)
Labour shortage in Malaysian construction industry is due to The Study Local Level Supply In Malaysia Construction Industry: Strategies In Improvement. In Malaysia, local youth would rather be unemployed despite working in the construction industry. This is attributed to the archaic employment practices, outdoor work and prevalence of the temporary and casual labour. The industry has been forced to rely on foreign labour, mostly from neighbouring countries. The government of Malaysia aims to reduce the number of foreign workers in the country from 1.84 million in 2005 to 1.5 million by 2010. It is envisaged that by this time, only 200,000 foreign workers will remains in the construction industry.The objectives of this study are; to identify the factors that led to the poor participation of local labour in the construction industry; to identify the critical factors that led to the poor participation of local labour; and to identify strategies to improve the participation of local labour in the construction industry. The method of the study involved literature review, data collection and an Average Index method was used for analysis. The data were gathered through questionnaire and interview. In conclusion, the respondents agreed that the first three major factors that led to the poor participation of local workforce in construction industry were related to uncomfortable, unsafe and unhealthy working conditions and temporary employment status. Five major strategies for the improvement on the local labour participation were to focus on training and advancement, employment status, enhance the safety practice and procedure and image of construction workers and site accommodations and services.